2018
DOI: 10.1155/2018/5423639
|View full text |Cite
|
Sign up to set email alerts
|

Weaning from Mechanical Ventilation in ARDS: Aspects to Think about for Better Understanding, Evaluation, and Management

Abstract: Acute respiratory distress syndrome (ARDS) is characterized by severe inflammatory response and hypoxemia. The use of mechanical ventilation (MV) for correction of gas exchange can cause worsening of this inflammatory response, called “ventilator-induced lung injury” (VILI). The process of withdrawing mechanical ventilation, referred to as weaning from MV, may cause worsening of lung injury by spontaneous ventilation. Currently, there are few specific studies in patients with ARDS. Herein, we reviewed the main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 100 publications
0
26
0
1
Order By: Relevance
“…In the most severe cases, the use of a Neuro-muscular blockade (NMB), prone position, and Extra-corporeal membrane oxygenation (ECMO) will be evaluated when there is refractory hypoxemia. These initial strategies are the key to successfully treating ARDS and therefore weaning success and reducing MV time [14].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the most severe cases, the use of a Neuro-muscular blockade (NMB), prone position, and Extra-corporeal membrane oxygenation (ECMO) will be evaluated when there is refractory hypoxemia. These initial strategies are the key to successfully treating ARDS and therefore weaning success and reducing MV time [14].…”
Section: Resultsmentioning
confidence: 99%
“…The presence of asynchrony during the weaning of ARDS patients from MV could be better quantified and distinguished. The presence of asynchrony, both quantity, and type, could be considered a predictor of MV weaning failure in patients with ARDS [14]. 35.4% of respondents agreed to monitor asynchrony for the treatment of ARDS, making it the least agreed from all the other possible solutions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason for the reintubation could be exacerbation of the respiratory workload owing to the lung brosis. It has been reported that the success rate of extubation is higher when respiratory effort and diaphragmatic muscle strength are added to the evaluation, besides the conventional extubation criteria [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…3 Weaning from mechanical ventilation is studied for many years and includes skills as well as thorough knowledge .Weaning can be simple in few patients but it may be difficult in others and may lead to prolonged weaning. 4 As associated mechanical ventilation complications, one must try to wean from mechanical ventilation as early as underlying cause is towards resolving side and spontaneous breathing can be maintained by patient. Weaning failure is an important concern because it may end in increased morbidity, prolonged hospital stay, increased cost and mortality.…”
Section: Introductionmentioning
confidence: 99%